Monitoring of trace elements in silverside ( Odontesthes bonariensis ) from pampasic ponds, Argentina - Vazquez, Fernanda Jimena (2015)
The presence of trace elements (Cr, Mnand Zn) in soft tissues (muscle, gills, scales, liver and gonads) of silverside(Odontesthes bonariensis), and its relation to the concentration of these elements, inwater of the Pampasic pondswere studied. Based on the results, the risk of poisoning by consumption of silverside fishwas calculated. Cr had ahigher concentration in the fish scales of most ponds, the gill being the secondary target organ. The highestconcentrations of manganese were found in gills, liver and fish scales. Gills and liver samples from Chascomúsponds had higher values of that metal than the rest of the ponds. In the ponds of Adela, Chis-Chis, and Barrancasthese concentrations were lower, with 14?34 μg/g in gills and 5?9 μg/g in liver. In Tablilla ponds, Mn concentrationin all organs of silverside was very variable. Zn was the metal with the highest concentration in all fish organsanalyzed with respect to the other trace elements studied. Considering the limits set by the Scientific Committeeon Food (SCF) for Cr at 0.03 mg/kg, Mn at 0.07 mg/kg and Zn at 1.57 mg/kg, and given a balanced diet, with aconsumption of twice a week, we could observe that in none of the cases the consumption of this species can beharmful to human health. Nevertheless, if we considered a daily consumption of this fish coming from Chascomúsponds, the limit of Mn could exceed the permitted levels and making it a human risk.